Adição de caseinato de sódio ao diluente de refrigeração de sêmen equino - Garcia, Victor Filgueiras Cruz [UNESP] (2016)
Among biotechnology for equine, semen cooling has an important role to be accessible and allow large genetic advancement. The use of cooling permits the use of studs without the need to transport stallions, reducing the costs and risks. However, to maintain low temperatures and adequate protection to create injuries to the use of extenders is required that will Interact whit the stability check sperm membrane. The study of these extenders answers questions about its mechanisms of action and protection, however, the extenders of greater availability and therefore more used in routine is based on milk skimmed milk powder, giving it a variable composition, difficult repeatability between lots. In this sense it is given for the search for substances that promote adequate protection of spermatozoa and make them more efficient diluents. The objetive of this review was to study the use of casein as a substitute for skimmed milk powder